The Reception of the Ottoman rule system in the Balkan states in the 19th-20th c. - Dymarski, Mirosław (Balcanica Posnaniensia. Acta et studia, 2014)
The article identifies the key elements of the reception of Ottoman rule in the Balkan states in the 19th and 20th c. The character of the centralized regimes established in the Balkan states defined as sultanism, autocracy, and authoritarianism, resulting from the absence of democratic tradition and an underdeveloped political awareness and culture. A characteristic feature of the Turkish system was the position of relatively free peasants, very different from that in Europe. The feature characteristic of the Ottoman tradition which survived in the Balkans the longest, until the end of the 20th century, was violence as an intrinsic component of political life and power often changing hands as a result of violence, assassinations, murders, etc.